2021
DOI: 10.21203/rs.3.rs-548056/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Valproic Acid on miRNAs Affecting Histone Deacetylase in a Model of Anaplastic Thyroid Cancer

Abstract: Thyroid cancer is the most common malignant tumor of the endocrine system seen in the thyroid gland. More than 90% of thyroid cancers comprise papillary thyroid cancer (PTC) and follicular thyroid cancer (FTC). Although anaplastic thyroid carcinoma (ATC) accounts for less than 2% of thyroid cancer. But patients' lifespan after diagnosis is about 6 months. Surgical interventions, radioactive iodine use, and chemotherapy are not sufficient in the treatment of ATC, so alternative therapies are needed. The WST-1 a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…It has also been shown that each miRNA has hundreds of target genes. Thus, even if the expression of a miRNA is changed, it has a signi cant impact on regulating target genes [12]. Their expression may be a marker of tissue health or disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that each miRNA has hundreds of target genes. Thus, even if the expression of a miRNA is changed, it has a signi cant impact on regulating target genes [12]. Their expression may be a marker of tissue health or disease.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the involvement of many miRNAs in diabetic complications such as retinopathy, nephropathy, neuropathy, and cardiovascular and pulmonary complications has been demonstrated [12,14]. Also decrease the expression of miRNA-155 in severe asthma and its inhibition in people with lung in ammation and ductal mucus secretion.…”
Section: Introductionmentioning
confidence: 99%